CHARACTERIZING SURFACE GROUND SETTLEMENT INDUCED BY UNDERGROUND TUNNEL EXCAVATION - Mohd Yusuf, Muhammad Firdaus (IRC, 2016)
The construction of underground tunnel, without a proper mitigation and proper design, a catastrophic event may be happen due to ground sedimentation. In the view of the issue of ground movement, it is possible to predict the ground sedimentation by plotting a Gaussian graph perpendicular alongside the direction of tunnel construction. The information obtained in the qualitative and quantitative data can be used to solve the geotechnical problems. This is to provide enough and reliable information to evaluate the performance of the structure and also the characteristics of the soil. The study is based at the location of Greater Kuala Lumpur (KL) and Selangor, specifically from Sungai Buloh Station, then across to KL and will end at Taman Desa Seroja Station for in total of 51km and 31 stations